SEBARAN DAN KARAKTERISTIK GENUSCOMBRETUM SEBAGAI SALAH SATU KOLEKSI TUMBUHAN WOODY CLIMBER DI KEBUN RAYA PURWODADI - Linda Wige Ningrum (Universitas Sebelas Maret, 2019)
The collection of woody climber plants in The Purwodadi Botanical Garden is one of the most exotic collection of plants, and is a main attraction for visitors to Purwodadi Botanical Garden. Woody Climber is also one of the groups of vines that are very abundant in the lowland tropics, and is a significant group of plants contributing oxygen and biomass. But there is not much research that discusses the woody climber. The existence of research on the distribution, and characteristics of the woody climber plants collection with the genus Combretum has a purpose to increase the collection of woody climber plants in Purwodadi Botanical Garden to be better known to the wider community, both as information material and scientific knowledge about woody climber plants. The method used in this research is by using descriptive observation and by studying literature. From the results of the data and observations, it was found that there were 2 types of plants identified, namely Combretum grandiflorum G. Don and Combretum indicum (L.) De Filipps. The physical characteristics were almost the same and the distribution was in tropical Asia and Africa, and there were many Combretum that had not been identified in Combretum sp. with 8 types from Java, 4 types from Maluku, 1 type from Kalimantan, and 3 types from Sulawesi. From these results it can be taken into consideration for future research on the identification of types of Combretum sp. The identification is expected to increase species recognition of the types of plant collections from the genus Combretum, as one of the woody climber plants collection in Purwodadi Botanical Gardens.